1953
DOI: 10.1111/j.1471-0307.1953.tb01303.x
|View full text |Cite
|
Sign up to set email alerts
|

HEAT RESISTANT BACTERIA IN RAW MILK: Part III.: The Proliferation of Thermoduric Organisms on Dairy Equipment

Abstract: Summary The results of five experiments designed to show the magnitude and rate of build‐up of thermoduric organisms on dairy equipment indicate that:— (1) Milk rinses of both hand milking utensils and milking machine clusters may contain over 10,000 thermoduric organisms per ml. within 2 to 4 days of absolute sterilisation, when the equipment is simply washed after milking in hot water or hot detergent and where the conditions of milking allow the introduction of a few thermoduric organisms into the milk at e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1955
1955
1967
1967

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…(a) I n relation to poor production methods The close relationship which exists between high thermoduric content of farm milk supplies and poor production methods continues to be the main reason for using the laboratory pasteurization test in laboratories associated with advisory work. The healthy udder is not a primary source of thermoduric bacteria (Gibson & Abd-El-Malek, 1940, 1957; Thomas, Thomas & Ellison, 1953), although some early reports from North America erroneously suggested that it was. Consequently, their presence in raw milk is nearly always due to contamination during production, and there is ample evidence to show that improperly cleansed milking and cooling equipment, and occasionally milk cans, are the most prolific sources.…”
Section: Significance Of Thermoduric Bacteria In Milkmentioning
confidence: 99%
See 1 more Smart Citation
“…(a) I n relation to poor production methods The close relationship which exists between high thermoduric content of farm milk supplies and poor production methods continues to be the main reason for using the laboratory pasteurization test in laboratories associated with advisory work. The healthy udder is not a primary source of thermoduric bacteria (Gibson & Abd-El-Malek, 1940, 1957; Thomas, Thomas & Ellison, 1953), although some early reports from North America erroneously suggested that it was. Consequently, their presence in raw milk is nearly always due to contamination during production, and there is ample evidence to show that improperly cleansed milking and cooling equipment, and occasionally milk cans, are the most prolific sources.…”
Section: Significance Of Thermoduric Bacteria In Milkmentioning
confidence: 99%
“…Correlation between thermoduric counts and atmospheric temperatures was observed by Thomas, Thomas, Grjffiths & Ellison (1952) and during the present investigation. This suggests that there is a more pronounced build-up of thermodurics on poorly cleansed equipment during warm weather, and some results obtained by them for fortnightly rinses of milking machine clusters on five farms confirmed this, but attempts to reproduce and demonstrate it with milking pails under laboratory conditions were unsuccessful (Thomas, Thomas & Ellison. 1953).…”
Section: Significance Of Thermoduric Bacteria In Milkmentioning
confidence: 99%